Monetary Policy and Sustainability: Historical Lessons and Contemporary Challenges - Giovanni Antonio Cossiga (Contemporary Research in Business, Management and Economics Vol. 9, 2024)
In this chapter, the role of monetary policy in addressing inflation and deflation from a sustainability perspective will be examined. The effectiveness of traditional interest rate adjustments in the current economic climate, influenced by geopolitical factors and speculation will be examined. In this chapter, the historical context of monetary policy, particularly the strategies employed by Volcker’s FED in the 1980s, is examined and contrasted with contemporary challenges. The findings suggest that while interest rate hikes can curb speculation, they may not effectively control inflation driven by international cost pressures. A re-evaluation of monetary strategies to align with sustainable economic practices may be required. A difficult moment for broader monetary policy, hit by the accusation of having caused the looming global recession with the rise in rates. But is it really like that? That is, would a more accommodative monetary policy have saved the economy for everyone? Probably a poorly posed question, because it is difficult to agree with those who want to blame the policies of the main banks for an economy that is not actually getting worse. Meanwhile, it should be emphasized that inflation due to international prices cannot be cured by manipulating interest rates. Nonetheless, major central banks made (on average) ten consecutive small jumps as inflation reared its head, resurrected by rising international prices. How can we now explain the interest rate shock to the real economy if the rates themselves have almost no effect on international price-driven inflation? What is perhaps meant is that with the proposed interest rate cut, we could avoid the reduction in prices due to the announced recession? But this hypothesis also does not seem to hold because the expected recession is not in sight and the stability of interest rates does not harm the economy. However, if central banks around the world insist on this unaccommodated tone, they must have their own reasons. Meanwhile, we can say that there was and still is a good reason, but it is only partly linked to the inflation of international prices. Indeed, the decision to repeatedly raise interest rates, which hovered around zero, was sacrosanct. It ended cheap credit, which in turn encouraged speculation in the prices of oil and rare metals. The pace of rising rates as stock market pressure eases is obviously less clear. The answer seems to be that central banks did not change their model after the victory over inflation achieved by Volcker’s FED, which raised rates above the inflation rate in the early 1980s. With the exceptional result of bringing inflation back under control and a record economic situation in the USA. But those were different times and another standard of inflation, linked to errors in the direction of the economy and not to the expected effects of speculation as in today’s context.